Effects of methyl violet dye on the growth and properties of zinc (tris) thiourea sulfate single crystals. (December 2018) - Shkir, Mohd; Ganesh, V.; Yahia, I.S.; Abd-Rabboh, Hisham S.M.; AlFaify, S.
Abstract: In this study, we investigated the monocrystal growth and characteristics of pure and methyl violet (MV) dyed zinc(tris) thiourea sulfate (ZTS) large size single crystals. The morphology of ZTS was modified in the presence of MV dye. The crystals were crushed for a finite time to obtain powders for X-ray diffraction analysis and the lattice parameters were determined. The crystals were analyzed based on Fourier transform-Raman spectroscopy measurements and the vibrational modes were identified. Some extra vibrational modes were observed due to the presence of the MV dye. Ultraviolet–visible–near infrared optical absorbance measurements were recorded and the band gap was calculated. A large band gap ∼4.31 eV was obtained for the ZTS crystals, which supports their possible application in electro-optic devices. Two absorption bands at around 584 nm (sharp) and ∼362 nm (broad) were also observed in the dyed crystals but not in the pure crystals, thereby indicating the interaction between the dye and ZTS. Photoluminescence (PL) emission studies were conducted at an excitation wavelength of 360 nm. PL emission peaks were observed at ∼433 nm in the pure crystals, and at ∼421 and 444 ± 5 nm in the dyed crystals. Differential scanning calorimetry demonstrated the increased melting temperature of ZTS in the presence of the dye. The dielectric constant, ac electrical conductivity, and mechanical strength were higher for the dyed crystals. Our results suggest that the dyed crystals may be more suitable for applications in opto-electronic devices compared with the pure crystals. Graphical abstract: Image 1 Highlights: Zinc(tris) thiourea sulfate (ZTS) crystals grown with methyl violet (MV). Structural and vibrational analyses confirmed the presence of MV dye. Two absorption bands detected at ∼362 nm and ∼584 nm in MV dyed crystals. Optical band gap values ranged from 4.29 to 4.33 eV. Photoluminescence, dielectric constant, and mechanical properties enhanced by MV.